ASSESSMENT OF RESULTS OF INDEPENDENT WORK STUDENTS IN PHYSICS IN THE CONDITIONS OF DISTANCE EDUCATION - Кузнєцова, Олена (SWorldJournal, 2023)
In recent years, the planned economy in our country has been replaced by market economic relations, the spectrum and structure of priority sectors of the economy have changed as a result of rapid development and the introduction of science-intensive tech